Acute severe headache: Association of herpes zoster meningitis and sinus vein thrombosis - Yurdakul Ertürk, Emine; İnce, Hülya and Albayrak, Davut (Journal of Surgery and Medicine, 2022)
The development of neurological complications related to varicella zoster virus (VZV) is rare, especially in immunocompetent children. We report a case of a 14-year-old male patient who presented with severe headache and diagnosed with acute aseptic meningitis and sinus vein thrombosis caused by reactivated VZV infection. Magnetic resonance (MR) venography identified limited flow, consistent with a thrombus in the right sigmoid sinus. Pressure of cerebrospinal fluid (CSF) was measured as high, with the PCR meningitis panel positive for VZV. These results show an association of VZV meningitis and sinus vein thrombus. Pediatric cases associated with aseptic meningitis and cerebral venous sinus thrombosis to varicella zoster reactivation have not yet been reported in the literature